Representation of Muslim Women in Online News: Study of Critical Discourse Analysis (NOBEL: Journal of Literature and Language Teaching, 2021)
This study mainly investigates the representation of Muslim women in online news. This article analyzes the data using Corpus Linguistics combined with Critical Discourse analysis (CL-CDA) supported by the topic modeling method. The data used are the news articles with approximately 50 thousand-word tokens. The selected news is news published in 2013-2021. The news was chosen because it can represent the social view of Muslim women since the news has the power to influence people’s perspectives. The results show that the direction of media representation towards Muslim women is gradually leading to a better direction. Factors that bring a negative image to Muslim women are generally due to the “black fashion,” which is associated with “terrorism.” However, modernization makes today’s Muslim women more critical. They have the freedom to express their opinion, take important positions, and support feminism and gender equality movements. The use of the niqab is generally prohibited in European countries because it is considered an extremist. But, The COVID-19 pandemic has also changed the image of the niqab to be more accepted in society. Niqab users are now seen as “face covering experts,” which attracts a lot of people.